Pattern for Malware remediation: A last dine of defence tool against malware in the global communication platform - Jonathan Pan; Chun Che Fung (International Telecommunications Society (ITS), 2012)
Malware is becoming a major problem to every organization that operates on the global communication platform. The malicious software programs are advancing in sophistication in many ways in order to defeat harden deployed defenses. When an organization's defense fails to keep this malice invasion out, the organization would incur significant amount of risks and damages. Risks include data leakage, inability to operate and tarnished corporate image. Damages include compensation costs to customers and partners, service unavailability and loss of customers' and partners' confidence in the organization. This in turn will affect the organization's business continuity. In order to manage the risks and damages induced by Malware incidents, incident responders are called upon to be the last line of defense against the digital onslaught assault. However incident responders are challenged too by the deep levels of knowledge, skills and experience required to contain the ever advancing and persistent Malware. This paper proposes the establishment of a Pattern template for Malware Remediation to aid incident responders to overcome their competency limitations in order to provide organizations the tool to repel Malware and to reduce the associated risks. Examples and details of the proposed patters are provided with discussions on future direction of the research work.
Keywords: 330; Pattern; Malware Remediation; Global Communication Platform